Paraíba State, Brazil: a hotspot of bryophytes - Germano, Shirley Rangel; Silva, Joan Bruno; Peralta, Denilson Fernandes (Phytotaxa, 2016)
A checklist for Paraíba bryophytes comprising 176 species (including 15 synonyms and the exclusion of three doubtful identifications), 86 genera, and 35 families is presented. This regional pool of species represents 19% of the Brazilian endemic species. We identified six species (not included in the Brazilian Red List) that require attention from a conservation viewpoint due to their rare distributions. The bryophyte assemblages are distributed according to precipitation and temperature gradients related to their distance from the coast, allied to stochastic processes. The present study identified deficits in collection efforts, especially in drier areas.